2021
DOI: 10.3390/nu13041256
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Decreases Hepcidin mRNA Gene Expression in STZ-Induced Diabetic Rats, Improving the Anemic State

Abstract: Diabetes is a disease with an inflammatory component that courses with an anemic state. Vanadium (V) is an antidiabetic agent that acts by stimulating insulin signaling. Hepcidin blocks the intestinal absorption of iron and the release of iron from its deposits. We aim to investigate the effect of V on hepcidin mRNA expression and its consequences on the hematological parameters in streptozotocin-induced diabetic Wistar rats. Control healthy rats, diabetic rats, and diabetic rats treated with 1 mgV/day were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
1
10
1
Order By: Relevance
“…The levels of proinflammatory parameters, leptin, C-reactive protein (CRP), interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-alpha (TNF-α) were determined in serum at day 35. These results are summarized in previous literature [ 14 ].…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…The levels of proinflammatory parameters, leptin, C-reactive protein (CRP), interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-alpha (TNF-α) were determined in serum at day 35. These results are summarized in previous literature [ 14 ].…”
Section: Resultssupporting
confidence: 52%
“…In identical working conditions, our research group described how treating rats with BMOV(IV) altered the homeostasis of Se [ 33 ], Mg [ 36 ] and Fe [ 34 ] and that these alterations were associated with changes in the antioxidant status. We also discovered that V treatment causes changes in serum levels of proinflammatory cytokines [ 14 ]. In the liver, we found that BMOV(IV) increased the activity of catalase (CAT), protein carbonyl groups and malonaldehyde (MDA) levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations